2004
DOI: 10.1002/ejoc.200400610
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenide–Lewis Acid Mediated Tandem Michael Aldol Reaction — an Alternative to the Morita–Baylis–Hillman Reaction and a New Development

Abstract: A tandem Michael aldol reaction mediated by a chalcogenide and Lewis acid was developed in three different types. Reactions of electron-deficient alkenes with aldehydes or α-keto esters in the presence of a sulfide and TiCl 4 gave α-chloromethyl aldols. Reactions of chalcogenide-enones with carbonyl compounds gave α-(α-hydroxyalkyl)enones (Morita-Baylis-Hillman adducts) after the work-up of the reaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…The catalytic role of enol ethers for the isomerization of 1 to II is reminiscent of the role that amines and phosphines play in the Baylis-Hillman reaction; [18] these Lewis bases promote a kind of aldol addition of unsaturated carbonyl compounds to aldehydes to provide the same unsaturated carbonyl compounds, the H on the Ca being replaced with 1-hydroxyalkyl groups. Accordingly, we examined a variety of Lewis bases in order to isolate or detect the intermediate II, or to accelerate the present [4+2] cycloaddition reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic role of enol ethers for the isomerization of 1 to II is reminiscent of the role that amines and phosphines play in the Baylis-Hillman reaction; [18] these Lewis bases promote a kind of aldol addition of unsaturated carbonyl compounds to aldehydes to provide the same unsaturated carbonyl compounds, the H on the Ca being replaced with 1-hydroxyalkyl groups. Accordingly, we examined a variety of Lewis bases in order to isolate or detect the intermediate II, or to accelerate the present [4+2] cycloaddition reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The metal-mediated domino Michael/aldol reaction of 1 to give 3 via the enolate 2 is the most widely utilized domino process (Scheme 8.1), whereby three stereogenic centers can be formed [3]. The reaction is an exceedingly reliable transformation, and allows for a great variety of reaction conditions [4].…”
Section: Metal-mediated Domino Michael/aldol Reactionsmentioning
confidence: 99%
“…The disadvantages of this reaction are slow reaction rate and long reaction time. It is often reported that a few days or a few weeks have been required for the reaction to be completed [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%